Can a national afforestation plan achieve simultaneous goals of biodiversity and carbon enhancement? Exploring optimal decision making using multi-spatial modeling. (March 2022) - Choi, Yuyoung; Lim, Chul-Hee; Krasovskiy, Andrey; Platov, Anton; Kim, Yoonji; Chung, Hye In; Kim, Moonil; Lee, Woo-Kyun; Shvidenko, Anatoly; Kraxner, Florian; Schepaschenko, Dmitry; Biging, Gregory S.; et al.
Abstract: There is a growing awareness of the need to integrate climate and biodiversity policies. As forests play an important role in mitigating biodiversity loss and climate change, numerous countries have established goals and are managing their forests to achieve them. However, forest management measures and land prioritization may differ depending on the target chosen, leading to conflicts. This research aims to seek optimized national afforestation plans in the Republic of Korea by assessing trade-offs between plant biodiversity persistence and carbon stocks. To this end, afforestation scenarios were spatially established based on the national forest management plans, with a target of 5800 ha expansion by 2022. Generalized Dissimilarity Modeling (GDM) and Global Forest Model (G4M) were applied to the selected afforestable regions to obtain scenarios that maximize biodiversity and carbon, respectively. Furthermore, another afforestation scenario that considers both objectives equally, was proposed using spatial simulated annealing (SSA) optimization algorithm to mitigate trade-offs. The constructed scenarios were compared, both spatially and quantitatively. As a result, the maximization scenarios were found to have few overlapping areas, with both scenarios resulting in ~50% trade-offs. These findings reveal that there is no universal solution and different management strategies are needed to enhance biodiversity persistence and carbon stocks. Thus, to strike a balance among the various goals, forest management requires a compromise solution to minimize trade-offs. Our national-scale assessment can help to guide future planning of national forest management with the consideration of the joint goals of biodiversity and carbon enhancement.